Fabrication and characterization of porcine bone-derived hydroxyapatite-alumina biocomposite - Apostol, Madeleine M.; Lobigan, Jovito Leo D.; Cruz, John Kenneth A. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
A bone grafts' main function is to support bone in growth, to induce bone healing, and to facilitate bone regeneration. Synthetic bone grafts are used since it can be easily modified according to the properties needed for a good bone substitute. For this study, a hydroxyapatite-alumina biocomposite was fabricated via sintering at 1000°C. Hydroxyapatite was extracted from porcine bones by means of calcination. Compositions of the three components and sintering time were varied to determine its effects in mechanical properties and biocompatibility. Fourier transform infrared spectroscopy, Scanning electron microscopy, compression test, and immersion test were done to characterize the biocomposite. Extracted hydroxyapatite has characteristic peaks very close to literature values and fabricated biocomposite was found to be compact and solid with minimal pores at the surface. Also, particles vary in sizes as expected since particle size was not considered in the first place. For the results of compression test, higher weight percent of alumina resulted to lower maximum stress and elastic modulus but higher fracture toughness while addition of starch unimproved the mechanical properties of the biocomposite. Lastly, the three-day immersion test using simulated body fluid yielded positive results as the samples were found to be stable with the highest weight loss being only 2.36%.
Thesis (B.S. Materials Engineering)--University of the Philippines Diliman
Keywords: Hydroxyapatite coating -- Biocompatibility; Biomedical materials